The Social Construction of Safe: Young Queer Men and HIV Knowledge - John P. Egan (Adult Education Research Conference, 2007)
Part of an international comparative ethnography of queer young men in Sydney Australia and Vancouver Canada, this paper examines these men’s learning about HIV/AIDS. Both the specifics of HIV infection (how) and the means by which to reduce one’s vulnerability to HIV (what) are analyzed. Overall these men showed consistently accurate understanding of the what, even when their understanding of the how was flawed. This knowledge was almost entirely acquired from queer programs and services.